Regulatory Gaps and Legal Enforcement Challenges on Deepfake Pornography as a Form of Digital Sexual Violence in Indonesia - Theodora Kristina Boleng; Adi Nur Rohman (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
The emergence of deepfake pornography, a development closely linked to artificial intelligence, has transformed the landscape of digital sexual assault. Perpetrators may employ machine learning algorithms to falsely portray a victim as being pornographically engaged without their consent or awareness. This research aims to examine the effective legislative frameworks addressing deepfake pornography in Indonesia, considering digital evidence and cross-border jurisdictions, and to evaluate the challenges encountered by law enforcement. This study utilises a normative juridical framework alongside qualitative analytical methods to analyse case studies, including incidents at Udayana and Semarang Universities in 2025, as well as pertinent legal sources such as the ITE Law, TPKS Law, and PDP Law. The study's findings indicate that the lack of standards and inadequacies in rule coordination persist as issues within Indonesia's legal system. TPKS and PDP have yet to tackle digital manipulation through artificial intelligence, whereas ITE has concentrated on the dissemination of ethical content. Moreover, law enforcement's efficacy is hindered by the absence of a national AI laboratory, limitations on digital forensic capabilities, and challenges in international coordination. Legal reform is essential to tackle these concerns; it must include new regulations concerning synthetic media offences, enhance digital forensics capabilities, and adopt victim-centered justice concepts to protect and restore victims' rights in the digital domain.